Effects of partially replacing fishmeal with corn gluten meal on growth, feed utilization, digestive enzyme activity, and apparent nutrient digestibility for juvenile white shrimp, Litopenaeus vannamei - Lin, Huaxing; Deng, Yingkai; Zhu, Dongwenjun; Yang, Qihui; Zhou, Xiaoqiu; Tan, Beiping; Feng, Lin; Chi, Shuyan (Frontiers in Veterinary Science, 2023)
This experiment was conducted to assess the possibility of replacing fishmeal (FM, Fishmeal content of the control group: 30%) with corn gluten meal (CGM) at the following levels: 0, 10, 20, 30, 40, and 60%. The experimental diets, formulated to be isonitrogenous and isocaloric, were studied for their effects on growth, feed utilization, digestive enzyme activity and apparent nutrient digestibility in juvenile white shrimps, Litopenaeus vannamei (initial mean weight = 0.71 ± 0.01 g). Seven hundred twenty healthy and uniformed-size shrimp were distributed to six groups of three replicates, each with 40 shrimp in each tank (0.5 m3). Each experimental diet was fed to shrimp four times daily to apparent satiation at 7:00, 11:30, 17:00, and 21:30, respectively, for 8 weeks. At the end of the experiment, the total weight of fish in each tank was weighed and randomly selected for testing, including fish nutrient composition and digestive enzyme activity. Results showed that no significant differences were observed in the weight gain rate (WGR), feed coefficient rate (FCR) and specific growth rate (SGR) of shrimp after 30% FM was replaced with CGM (P > 0.05), but these indicators significantly decreased at higher replacement rates. As CGM content increased, the content of crude protein and phosphorus in the shrimp decreased significantly (P < 0.05), whereas the crude fat content first increased significantly and then decreased (P < 0.05). Compared to the control group, the protease activity was significantly lower in the 40% group and the lipase activity was significantly lower in the 60% group (P < 0.05). Amylase activity was significantly increased with increasing CGM levels (P < 0.05). The digestibility of protein and lipid was significantly reduced by CGM replacement of more than 30% FM (P < 0.05). As CGM content increased, the digestion of energy and dry matter was first significantly increased and then significantly decreased (P < 0.05). In the 30, 40, and 60% groups, the digestibility of all amino acids (AA), except methionine (Met), arginine (Arg) and serine (Ser), was significantly lower than in the control group (P < 0.05). In summary, FM could be partially replaced by CGM in the feed of L. vannamei. Based on the broken-line regression analysis of WGR, the optimal dietary CGM replacement was 27.47%.